Soluble form of ICAM-1, VCAM-1, E- and L-selectin in human milk - Kyriaki Xyni; Dimitrios Rizos; Galini Giannaki; Angeliki Sarandakou; Iphigenia Phocas; George Creatsas (Mediators of Inflammation)
In breast milk and paired serum from 70 lactating women and 40 of their term, infection-free neonates, on the 2nd and 5th day postpartum slCAM-1, sVCAM-1, sE- and sL-selectin were measured by ELISA and compared with those in 26 healthy adults (controls). Seven infant formulas and fresh milk from five cows were also analyzed. Human colostrum values of slCAM-1, sVCAM-1 (similar to those in maternal and control serum), sE-selectin and sL-selectin (˜10 and ˜100 times lower than in maternal and control serum) were significantly higher than those in milk, while they varied widely. None of the adhesion molecules was detected in fresh cow’s milk or infant formulas. Exclusively breast-fed infants showed significantly higher values of slCAM-1 and sL-selectin on the 2nd day of life than those supplemented also with formula. Only slCAM-1 values correlated positively between colostrum and time-matched maternal serum. These findings show in human milk important amounts of slCAM-1 and sVCAM-1 but minimal amounts of sE- and sL-selectin, which could affect the immune system of the neonate.